International recognition of the Chronic Otitis Media Questionnaire 12. Issue 6 (27th March 2017) - Kosyakov, S I; Minavnina, J V; Phillips, J S; Yung, M W
Abstract: Objective: The Chronic Otitis Media Questionnaire 12 was developed initially in the UK to assess patient-reported health-related quality of life associated with chronic otitis media. This study aimed to determine whether this tool is applicable to the Russian population, which has a materially different healthcare system. Method: A total of 108 patients with different forms of chronic otitis media completed the Russian Chronic Otitis Media Questionnaire 12. Results: The average Russian Chronic Otitis Media Questionnaire 12 score was 19.4 (standard deviation = 8.3). The internal consistency of the Russian Chronic Otitis Media Questionnaire 12 was high, with a Cronbach's alpha value of 0.860. Conclusion: The Russian version of the Chronic Otitis Media Questionnaire 12 was found to be a reliable tool for the assessment of health-related quality of life in patients with chronic otitis media. This sets the scene for international collaboration, using this tool to assess the effectiveness of surgical treatments even amongst countries with different healthcare systems.